1993
DOI: 10.7326/0003-4819-119-8-199310150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokine and Endotoxin Levels Correlate with Survival in Patients with the Sepsis Syndrome

Abstract: Patients with the sepsis syndrome have detectable levels of circulating TNF-alpha, IL-1, IL-6, and lipopolysaccharide independent of culture-documented infection. Lipopolysaccharide and cytokines may play a pathogenic role in sepsis, and the combination of several elevated factors may be important in determining patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
513
7
38

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,014 publications
(595 citation statements)
references
References 0 publications
37
513
7
38
Order By: Relevance
“…However, similar to an induction of IFN-g and IL-12 (not measured in our study) observed with B. henselae stimulation in rodents 26 , our series of patients showed a significant initial elevation of IFN-g (Fig. 2) and a non-significant elevation of TNF-α (Table 1) as part of the inflammatory process that also can be seen in other gram-negative infections 4,19 .…”
Section: Discussionmentioning
confidence: 70%
“…However, similar to an induction of IFN-g and IL-12 (not measured in our study) observed with B. henselae stimulation in rodents 26 , our series of patients showed a significant initial elevation of IFN-g (Fig. 2) and a non-significant elevation of TNF-α (Table 1) as part of the inflammatory process that also can be seen in other gram-negative infections 4,19 .…”
Section: Discussionmentioning
confidence: 70%
“…For example, the evaluation of a combination of elevated cytokine levels has been shown to be more accurate than any single elevated cytokine level in determining patient survival. 23 However, many tests, especially for cytokines, are very expensive, which may preclude their routine use. An ideal biological marker of sepsis would fulfill rigorous criteria: it must be specific and sensitive; it must be able to be rapidly performed; and it must be of low cost.…”
Section: Strem-1: the Biological Marker Of Infection?mentioning
confidence: 99%
“…The plasma endotoxin concentration is reported to be increased in gram-negative and gram-positive infections. 24 In view of the fact that we used the caecal ligation and puncture model, it is probable that the shock state was induced by a gram-negative bacterial infection. 9…”
Section: Discussionmentioning
confidence: 99%